2021
DOI: 10.1111/1755-6724.14697
|View full text |Cite
|
Sign up to set email alerts
|

Fluid‐driven Hydrovolcanic Activity along Fracture Zones and near Seamounts: Evidence from Deep‐sea Fe‐rich Spherules, Central Indian Ocean Basin

Abstract: An insight on occurrence of Fe-rich spherules from the Central Indian Ocean Basin (CIOB) provides an understanding of their distribution at a water depth of >5,000 m. In the present study, Fe-rich spherules are identified to occur in two different sediment types (i.e., siliceous and pelagic) and tectonic settings (i.e. near seamounts and fracture zones). These are single spheres or aggregates, of different sizes (63 to 390 µm) and show textural variability (smooth/ quenched, brickwork, corkscrew, interlocking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Notably, magnetite spherules have been documented in hydrothermal vents associated with sea-floor volcanism. These records include magnetite-hematite granules in the Earth’s oldest hydrothermal vent precipitates in the Nuvvuagittuq belt in Quebec, Canada, and magnetite spherules in sediments from the Central Indian Ocean Basin (CIOB). It has been suggested that the magnetite spherules reported at CIOB formed as a result of hydrovolcanic processes involving Fe-rich hydrothermal emanations. These spherules vary from smooth-surfaced low-crystallinity structures to crystalline particles showing well-developed magnetite crystals and dendritic patterns. , The low-crystallinity spherules are interpreted as having formed by rapid quenching processes, whereas well-crystallized spherules would have experienced slower cooling, leading to the development of euhedral magnetite crystals .…”
Section: Formation Of Magnetite Microspheresmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, magnetite spherules have been documented in hydrothermal vents associated with sea-floor volcanism. These records include magnetite-hematite granules in the Earth’s oldest hydrothermal vent precipitates in the Nuvvuagittuq belt in Quebec, Canada, and magnetite spherules in sediments from the Central Indian Ocean Basin (CIOB). It has been suggested that the magnetite spherules reported at CIOB formed as a result of hydrovolcanic processes involving Fe-rich hydrothermal emanations. These spherules vary from smooth-surfaced low-crystallinity structures to crystalline particles showing well-developed magnetite crystals and dendritic patterns. , The low-crystallinity spherules are interpreted as having formed by rapid quenching processes, whereas well-crystallized spherules would have experienced slower cooling, leading to the development of euhedral magnetite crystals .…”
Section: Formation Of Magnetite Microspheresmentioning
confidence: 99%
“…These records include magnetite-hematite granules in the Earth’s oldest hydrothermal vent precipitates in the Nuvvuagittuq belt in Quebec, Canada, and magnetite spherules in sediments from the Central Indian Ocean Basin (CIOB). It has been suggested that the magnetite spherules reported at CIOB formed as a result of hydrovolcanic processes involving Fe-rich hydrothermal emanations. These spherules vary from smooth-surfaced low-crystallinity structures to crystalline particles showing well-developed magnetite crystals and dendritic patterns. , The low-crystallinity spherules are interpreted as having formed by rapid quenching processes, whereas well-crystallized spherules would have experienced slower cooling, leading to the development of euhedral magnetite crystals . However, in addition to these temperature-mediated processes, it is likely that pressure drops related to the activity of these hydrovolcanic systems have also played a key role triggering magnetite precipitation, as demonstrated in magnetite solubility experiments under hydrothermal conditions …”
Section: Formation Of Magnetite Microspheresmentioning
confidence: 99%
See 2 more Smart Citations